Effect of jatropha-placenta-cmc formulation on second-degree burn wound healing in rats: Fibroblast growth factor expression - Mellyna Mellyna; Juniarti Juniarti; Nunung Ainur Rahmah; Restu Syamsul Hadi; Nabila Pyrenina Thamrin (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Second-degree burns require effective topical therapy to accelerate tissue regeneration and reduce complications. Current treatments remain limited by side effects and suboptimal regenerative outcomes. This study aimed to evaluate the effectiveness of a combination gel of Jatropha multifida L. latex, placenta extract, and carboxymethyl chitosan (JM–P–CMC) on burn wound healing by assessing fibroblast growth factor (FGF) expression, fibroblast count, and collagen density. Research Methodology: A post-test-only controlled experimental design was conducted using 18 male Sprague-Dawley rats, allocated into 6 groups. Standardised second-degree burns (1×1 cm) were induced and treated for 15 days. Histological and immunohistochemical analyses were performed at days 5, 10, and 15. Data were analysed using the Kruskal–Wallis and Mann–Whitney tests (α=0.05), with effect sizes expressed as median differences (%) and 95% confidence intervals (CI). Results: The JM–P–CMC group demonstrated significantly higher FGF expression compared to saline (Day 15 median: 75 vs 33; =42%; p=0.0015; 95% CI: 18–60). Fibroblast counts were also significantly increased (median: 55 vs 17; =38%; p=0.0001; 95% CI: 20–64). Collagen density was markedly higher in the intervention group (58.83% vs 21.70%; p<0.01). A strong positive correlation was observed between fibroblast count and collagen density on day 10, whereas FGF showed an inverse regulatory relationship with collagen during the remodelling phase. Conclusion: The JM–P–CMC gel significantly enhances burn wound healing through modulation of FGF expression, fibroblast proliferation, and collagen deposition. This formulation represents a promising, safe, and cost-effective alternative for topical burn management and supports the integration of bioactive-based therapies into clinical and nursing practice.